LEARNING VOCABULARY THROUGH APPLICATIONS ON SMARTPHONES - Kudritskaya, M.I.; Kabulova, Zh.Sh. (PUBLISHINGS of Kostanay State Pedagogical University, 2019)
This article describes applications as a means of enriching the vocabulary of a foreign language. The analysis revealed a number of applications used to enrich vocabulary, to test knowledge at different stages of a lesson and with different levels of language. Teaching through mobile applications is often overlooked in the classroom and underrepresented in educational materials and teacher education courses. The presence and openness of such a problem when teaching a foreign language determined its relevance and, as a consequence, the choice of topic for the selected article.
Keywords: mobile learning; smartphones; applications; enriching vocabulary